2011
DOI: 10.1155/2011/853560
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of One‐Way and Two‐Way Coupling Methods for Numerical Analysis of Fluid‐Structure Interactions

Abstract: The interaction between fluid and structure occurs in a wide range of engineering problems. The solution for such problems is based on the relations of continuum mechanics and is mostly solved with numerical methods. It is a computational challenge to solve such problems because of the complex geometries, intricate physics of fluids, and complicated fluid-structure interactions. The way in which the interaction between fluid and solid is described gives the largest opportunity for reducing the computational ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(82 citation statements)
references
References 11 publications
0
73
0
1
Order By: Relevance
“…For two-way coupling calculations, uid and wind pressure is transferred to the structure and the displacement of the structure is also transferred to the uid solver [19]. e properties of steel material are employed for the wind tower.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…For two-way coupling calculations, uid and wind pressure is transferred to the structure and the displacement of the structure is also transferred to the uid solver [19]. e properties of steel material are employed for the wind tower.…”
Section: 3mentioning
confidence: 99%
“…FSI analyses can be classi ed as one-way and two-way coupling models. In the one-way coupling type, only the uid pressure is transferred to the structure solver, and in the two-way coupling type, the displacement of the structure is also transferred to the uid solver [19].…”
Section: Introductionmentioning
confidence: 99%
“…where: the stresses, σ xx = E L xx , σ xη = G xη , σ xζ = G xζ , and the strains, xx = 11 , xη = 2 12 The gravitational potential energy of the ith element is given by:…”
Section: Structural Modelmentioning
confidence: 99%
“…The generation terms of k and ω are G k = min(G k , 10ρβ * kω) and G ω = α ω ν t G k , respectively, with G k = −ρu i u j ∂u j /∂x i , S k and S ω are the source terms for k and ω, respectively, ν t = k/ω, and the term u i u j is the Reynolds stress tensor [12]; the dissipation terms are, Y k = ρβkω and Y ω = ρβkω 2 ; and the cross diffusion term that blends the two models is given by D ω = 2(1 − F 1 )ρσ ω,2 1 ω ∂k ∂x j ∂ω ∂x j σ k and σ ω are the turbulent Prandtl's numbers; µ and µ t are dynamic and turbulent viscosity; and the coefficients β * , β, α ω , σ ω,2 and F 1 are damping functions, and can be determined based on Menter et al [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Benra, Dohmen, Pei, Schuster, and Wan (2011) demonstrated the advantages of FSI by using it to predict the deflection behavior of a cantilever beam which could not be predicted using single-domain analysis. Siba, Wanmahmood, Zakinuawi, Rasani, and Nassir (2016) investigated the damage caused to orifice and pipe structures by fluid-induced vibrations and showed that FSI analysis captures drastically changing vorticity and swirling activities more accurately than conventional methods.…”
Section: Introductionmentioning
confidence: 99%